Middle-infrared-band low-infrared-emissivity material and preparation method thereof

By applying polyurethane resin, conductive film and anti-rust paint layer on the base layer in turn to form a low infrared emissivity coating, the problems of high emissivity and poor weather resistance of existing materials are solved, and low emissivity and high light transmittance in the 8-14μm band are achieved, which is suitable for infrared stealth and intelligent thermal management.

CN120534022APending Publication Date: 2025-08-26CHINA SHIPBUILDING INDUSTRY CORPORATION NO725 RESEARCH INSTITUTE
View PDF 1 Cites 0 Cited by

Patent Information

Application Number
CN202510842858.0
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2025-06-23
Publication Date
2025-08-26

AI Technical Summary

Technical Problem

The existing low infrared emissivity materials have high emissivity in the 8-14μm band and complex preparation process. The materials are prone to falling off in harsh environments and have poor weather resistance.

Method used

The structure of low emissivity composite layer, anti-rust paint layer and base layer is adopted, and materials such as polyurethane resin, conductive film and nanometal particles are used to form a low emissivity coating by coating and curing, and the thickness of the material is controlled to adjust the emissivity.

Benefits of technology

It achieves a low infrared emissivity in the 8-14μm band, the material has good stability in harsh environments, strong adhesion, high light transmittance, and simple preparation process.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN120534022A_ABST
    Figure CN120534022A_ABST
Patent Text Reader

Abstract

The invention provides a middle-infrared-band low-infrared-emissivity material and a preparation method thereof. The middle-infrared-band low-infrared-emissivity material comprises a low-emissivity composite layer, an anti-rust paint layer and a base layer which are sequentially connected. The low-emissivity composite layer is one of a first low-emissivity layer, a second low-emissivity layer and a second low-emissivity layer; the raw material of the first low-emissivity layer is one or more of polyurethane resin, fluorocarbon resin and epoxy resin; the raw material of the second low-emissivity layer is one of a conductive film and compound slurry; the conductive thin film is one or more of antimony-doped tin oxide, fluorine-doped tin oxide, indium tin oxide, aluminum-doped zinc oxide and a silver nanowire transparent thin film. The polyurethane resin provided by the invention can reduce the introduction of oxygen-containing functional groups, so that the polyurethane resin has lower emissivity and good light transmittance in the wave band of 8-14 microns, and the low emissivity of the material can be controlled by regulating and controlling the thickness of the polyurethane resin layer.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The present invention relates to the technical field of functional materials, and in particular to a mid-infrared band low infrared emissivity material and a preparation method thereof. Background Art

[0002] As infrared detection technology and thermal management requirements continue to escalate, reducing target infrared thermal radiation to control radiant temperature has become a key technical direction. According to the Stefan-Boltzmann law, reducing the surface emissivity of an object is the key path to reducing infrared radiation intensity and achieving temperature regulation. The 8-14μm wavelength is the atmospheric transparency window in the mid-infrared band, a core band for surface thermal radiation and infrared detection. Achieving low emissivity in this band can significantly improve target thermal management capabilities. However, existing low-emissivity material technologies still have significant limitations.

[0003] In terms of performance, while some materials achieve low emissivity through nanoparticle doping, significant particle agglomeration occurs, leading to increased surface roughness in the coating and, in turn, enhanced infrared scattering and absorption. Regarding environmental adaptability, existing materials are susceptible to oxidation and hydrolysis reactions at the interface between the material and the substrate under harsh conditions such as high temperature, high humidity, and salt spray, causing material shedding and a sharp increase in emissivity. Furthermore, the materials have poor weather resistance and are prone to failure after prolonged exposure to ultraviolet light.

[0004] Publication number is CN 112920697 B discloses a kind of preparation method of super-hydrophobic low infrared emissivity coating, with flaky Al powder as functional pigment, nano-SiO for micro-nano structure modifier, hydrogenated silicone oil (HCSO) modified polyurethane (PU) is adhesive, polyether polyol is curing agent, and absolute ethanol is diluent, above-mentioned raw materials are placed in disposable plastic cup and are fully stirred through glass rod, then after being fully dispersed with ultrasonic wave, viscosity is adjusted to coating in a straight line and continuously flows down with appropriate diluent, obtain super-hydrophobic low infrared emissivity coating, subsequently, by glass rod scraping method, 0.8~1.2g above-mentioned coating is coated on prepared substrate, 5h is dried at room temperature, then placed in 80 DEG C baking oven 10h, obtain super-hydrophobic low infrared emissivity coating. Super-hydrophobic low infrared emissivity coating of the prior art not only has complicated preparation process, and is higher in the emissivity of 8-14 μm wave band. Summary of the Invention

[0005] In view of this, the present invention aims to provide a mid-infrared band low infrared emissivity material and its preparation method to solve the problem that the super hydrophobic low infrared emissivity coating in the prior art is not only complicated in preparation process but also has a high emissivity in the 8-14μm band.

[0006] To achieve the above object, the technical solution of the present invention is achieved as follows:

[0007] A mid-infrared band low-infrared emissivity material, comprising a low-emissivity composite layer, an anti-rust paint layer, and a base layer connected in sequence; the low-emissivity composite layer is one of a first low-emissivity layer, a first low-emissivity layer, and a second low-emissivity layer; the raw material of the first low-emissivity layer comprises one or more of polyurethane resin, fluorocarbon resin, and epoxy resin; the raw material of the second low-emissivity layer is one of a conductive film and a compound slurry; the conductive film is one or more of antimony-doped tin oxide, fluorine-doped tin oxide, indium tin oxide, aluminum-doped zinc oxide, and a silver nanowire transparent film.

[0008] The materials in this setup have low emissivity in the 8-14 μm band and good light transmittance.

[0009] Furthermore, the polyurethane resin is a polymer resin having a carbamate group.

[0010] Furthermore, the polyurethane resin includes a component A containing a polyol, a component B containing an isocyanate, and a solvent component C, wherein component A is composed of one or more of polytetrahydrofuran, polycaprolactone diol, and polyolefin diol; component B is composed of one or more of isophorone diisocyanate, hexamethylene diisocyanate, and isophorone diisocyanate trimer; and component C is composed of one or more of xylene, cyclohexanone, and butyl acetate.

[0011] Furthermore, the mass ratio of component A, component B and component C is 1: (0.9~1.3): (1~2).

[0012] Furthermore, the thickness of the first low emissivity layer is 20-40 μm.

[0013] Furthermore, the raw material of the anti-rust paint layer is H44-61 epoxy anti-rust primer.

[0014] Furthermore, the compound slurry is compounded by nano-metal particles, fluorocarbon resin, and curing agent, the nano-metal particles are composed of one or more of nano-silver powder, nano-aluminum powder, nano-zinc powder, nano-copper powder, and nano-titanium powder, and the curing agent is N3390.

[0015] Furthermore, the mass ratio of the nano-metal particles, fluorocarbon resin and curing agent is 8-15:10:1-5.

[0016] A method for preparing the mid-infrared band low-infrared emissivity material as described above, wherein the low-emissivity composite layer comprises a first low-emissivity layer and a second low-emissivity layer, and the raw material of the first low-emissivity layer is polyurethane resin, specifically comprising the following steps:

[0017] S1, preparing polyurethane resin;

[0018] S2. Pre-treat the base layer and apply anti-rust paint to the surface of the base layer;

[0019] S3, pasting or coating the raw material of the second low emissivity layer on the base layer processed in step S2;

[0020] S4, coating the polyurethane resin on the base layer of step S3;

[0021] S5. Curing the base layer obtained in step S4 at a curing temperature of 20-80°C.

[0022] The preparation method of this device is simple, and the prepared material has low emissivity and good light transmittance.

[0023] Furthermore, in step S3, when the raw material of the second low emissivity layer is a conductive film, it is placed on the base layer by pasting; when the raw material of the second low emissivity layer is a compound slurry, it is placed on the base layer by coating.

[0024] Compared with the prior art, the mid-infrared band low infrared emissivity material and the preparation method thereof described in the present invention have the following advantages:

[0025] 1) The polyurethane resin of the present invention can reduce the introduction of oxygen-containing functional groups, resulting in low emissivity and good light transmittance in the 8-14 μm band. Furthermore, the low emissivity of the material can be effectively controlled by adjusting the thickness of the polyurethane resin layer.

[0026] 2) The present invention can reduce the infrared emissivity of the material in the 8-14μm band to 0.2 by sequentially loading anti-rust paint, ITO conductive film, and polyurethane resin on the base layer;

[0027] 3) The present invention coats an anti-rust paint layer on the base layer, and the material can achieve an infrared emissivity of 0.6-0.9 in the 8-14μm band. The anti-rust paint layer and emissivity slurry are sequentially arranged on the base layer, and the material can achieve an infrared emissivity of 0.4-0.6 in the 8-14μm band. The anti-rust paint layer, ITO film, and polyurethane resin are sequentially coated on the base layer, and the material can achieve an infrared emissivity of 0.2-0.4 in the 8-14μm band. Figure 1 shown. BRIEF DESCRIPTION OF THE DRAWINGS

[0028] Figure 1 A flow chart for the preparation of materials of the present invention;

[0029] Figure 2 is a structural diagram of the material of the present invention, wherein Figure 2 (a) is a structural diagram of materials prepared in Examples 1 to 3 of the present invention, Figure 2 (b) is a structural diagram of materials prepared in Examples 4 to 9 of the present invention;

[0030] Figure 3 The thickness of the polyurethane resin coating of the present invention corresponds to the infrared emissivity of the material at 8-14 μm, where Figure 3 (a) is a material relationship diagram prepared in Examples 1 to 3 of the present invention; Figure 3 (b) is a material relationship diagram prepared in Examples 4 to 6 of the present invention; Figure 3 (c) is a material relationship diagram prepared in Examples 7 to 9 of the present invention; Figure 3 (d) Figure 3 (a) Figure 3 (b) Figure 3 (c) Summary diagram.

[0031] Figure 4 4 is a graph showing the relationship between the thickness of the polyurethane resin coating and the light transmittance and haze of Examples 7 to 9 of the present invention.

[0032] Description of reference numerals:

[0033] 10-first low emissivity layer, 20-second low emissivity layer, 30-anti-rust paint layer, 40-base layer. DETAILED DESCRIPTION

[0034] In order to make the above-mentioned objects, features and advantages of the present invention more obvious and easy to understand, specific embodiments of the present invention are described in detail below with reference to the accompanying drawings.

[0035] like Figures 1 and 2 As shown, the present invention proposes a mid-infrared band low-infrared emissivity material, comprising a low-emissivity composite layer, an anti-rust paint layer 30, and a base layer 40 connected in sequence; the low-emissivity composite layer is one of a first low-emissivity layer 10, a first low-emissivity layer 10, and a second low-emissivity layer 20.

[0036] Specifically, when the low-emissivity composite layer is the first low-emissivity layer 10 and the second low-emissivity layer 20 , the second low-emissivity layer 20 is located between the first low-emissivity layer 10 and the anti-rust paint layer 30 .

[0037] Specifically, the raw material of the first low emissivity layer includes one or more of polyurethane resin, fluorocarbon resin, and epoxy resin.

[0038] Preferably, the raw material of the first low emissivity layer is polyurethane resin, which is a polymer resin having a carbamate group.

[0039] More specifically, the polyurethane resin includes component A containing polyol, component B containing isocyanate, and component C as a solvent. Currently, commercially available polyurethanes have a special oxygen-containing functional group structure, which makes them have a higher emissivity in the 8-14 μm band. The polyurethane used in the present invention reduces the introduction of oxygen-containing functional groups, so that it has a lower emissivity in the 8-14 μm band and has good light transmittance.

[0040] More specifically, component A is composed of one or more of polytetrahydrofuran, polycaprolactone diol, and polyolefin diol; preferably, component A is polyolefin diol.

[0041] More specifically, component B is composed of one or more of isophorone diisocyanate, hexamethylene diisocyanate, and isophorone diisocyanate trimer; preferably, component B is isophorone diisocyanate trimer.

[0042] More specifically, component C is composed of one or more of xylene, cyclohexanone, and butyl acetate; preferably, component C is xylene and cyclohexanone in a volume ratio of 1:1.

[0043] More specifically, the mass ratio of component A, component B, and component C is 1:(0.9-1.3):(1-2).

[0044] More specifically, the thickness of the first low-emissivity layer is 20-40 μm.

[0045] Specifically, the raw material of the second low emissivity layer is one of a conductive film and a compound slurry.

[0046] More specifically, the conductive film is one or more of antimony-doped tin oxide (ATO), fluorine-doped tin oxide (FTO), indium tin oxide (ITO), aluminum-doped zinc oxide (AZO), and silver nanowire transparent film. Preferably, the conductive film is an ITO film.

[0047] Specifically, the raw material of the base layer is one or more of metal plates and composite material plates, preferably metal plates with excellent electrical conductivity, including the first one of iron plates, aluminum plates, steel plates, copper plates, silver plates, and alloy plates.

[0048] Specifically, the raw material of the anti-rust paint layer is H44-61 epoxy anti-rust primer.

[0049] Specifically, the compounded slurry is composed of nano-metal particles, a fluorocarbon resin, and a curing agent. The nano-metal particles are composed of one or more of nano-silver powder, nano-aluminum powder, nano-zinc powder, nano-copper powder, and nano-titanium powder. Preferably, the nano-metal particles are nano-aluminum powder. The curing agent is N3390. Preferably, the fluorocarbon resin is GK570.

[0050] Specifically, the mass ratio of the nano-metal particles, fluorocarbon resin and curing agent is 8-15:10:1-5.

[0051] Specifically, the epoxy resin is a polymer resin containing two or more epoxy groups in the molecule, and its main characteristic is the -O-CH2-CH- group. Due to its special epoxy structure, the epoxy resin has good heat resistance and weather resistance.

[0052] Specifically, the epoxy resin is composed of one or more of bisphenol epoxy resin, novolac epoxy resin and alicyclic epoxy resin; the curing agent is composed of one or more of aromatic diamine and polyether amine; the epoxy resin is a commercially available component, and the first low emissivity layer is obtained by coating after uniformly mixing the epoxy resin and the curing agent in a ratio of 5:1 at room temperature.

[0053] Specifically, fluorocarbon resin is a type of polymeric synthetic material containing fluorine atoms in the main chain or side chain. Due to its unique C-F bond, it has excellent weather resistance, chemical stability, and low surface energy. The fluorocarbon resin is one or more of GK570, JF-4X, and ZHF-100, and the curing agent is one or more of N3390, N3600, and T1890, preferably the first of GK570 and N3390. The fluorocarbon resin is also a commercially available resin. The first low-emissivity layer is formed by uniformly mixing GK570 and the curing agent N3390 at room temperature and then coating. The mass ratio of the two is in the range of 10:1-2:1, preferably 6:1.

[0054] A method for preparing the mid-infrared band low-infrared emissivity material as described above, wherein the low-emissivity composite layer comprises a first low-emissivity layer and a second low-emissivity layer, and the raw material of the first low-emissivity layer is polyurethane resin, specifically comprising the following steps:

[0055] S1, preparing polyurethane resin;

[0056] Specifically, component A, component B, and component C are mixed in a certain mass ratio at a mixing temperature of 20°C;

[0057] S2. Pre-treat the base layer and apply anti-rust paint to the surface of the base layer;

[0058] Specifically, pretreatment refers to cleaning surface impurities with ethanol.

[0059] S3, pasting or coating the raw material of the second low emissivity layer on the base layer processed in step S2;

[0060] Specifically, when the raw material of the second low emissivity layer is a conductive film, it is set on the base layer by pasting; when the raw material of the second low emissivity layer is a compound slurry, it is set on the base layer by brushing or spraying.

[0061] S4, coating the polyurethane resin on the base layer of step S3.

[0062] S5. Curing the base layer obtained in step S4 at a curing temperature of 20-80°C.

[0063] The technical solutions in the embodiments of the present invention will be clearly and completely described below in conjunction with the embodiments of the present invention.

[0064] Example 1

[0065] This embodiment provides a method for preparing a low-infrared emissivity material in the mid-infrared band, comprising sequentially connecting a first low-emissivity layer, an anti-rust paint layer, and a base layer. The raw materials of the first low-emissivity layer, the anti-rust paint layer, and the base layer are shown in Table 1. The method specifically comprises the following steps:

[0066] Step 1: Prepare polyurethane resin by mixing component A, component B, and component C in a mass ratio of 1:1.2:1 at a mixing temperature of 20°C;

[0067] Step 2: Pre-treat the metal base plate, clean the surface impurities with ethanol, and apply H44-61 epoxy anti-rust paint to the base surface;

[0068] Step 3: Spraying the polyurethane resin onto the base layer, controlling the thickness of the polyurethane resin coating to 20 μm;

[0069] Step 4: Curing the base layer obtained in step 3 at a curing temperature of 30°C.

[0070] The material obtained in this embodiment has been tested and the emissivity of the material in the 8-14μm band is 0.6. Figure 3 (a) shown.

[0071] Example 2

[0072] The difference between this embodiment and embodiment 1 is that in step 3, the thickness of the polyurethane resin coating is 30 μm; the material obtained in this embodiment has been tested and the emissivity of the material in the 8-14 μm band is 0.7. Figure 3 (a) shown.

[0073] Example 3

[0074] The difference between this embodiment and embodiment 1 is that in step 3, the thickness of the polyurethane resin coating is 40 μm; the material obtained in this embodiment has been tested and the emissivity of the material in the 8-14 μm band is 0.8. Figure 3 (a) shown.

[0075] Example 4

[0076] This embodiment provides a method for preparing a low-infrared emissivity material in the mid-infrared band, comprising sequentially connecting a first low-emissivity layer, a second low-emissivity layer, an anti-rust paint layer, and a base layer. The raw materials of the first low-emissivity layer, the second low-emissivity layer, the anti-rust paint layer, and the base layer are shown in Table 1. The method specifically comprises the following steps:

[0077] Step 1: Prepare polyurethane resin by mixing component A, component B, and component C in a mass ratio of 1:1.2:1 at a mixing temperature of 20°C;

[0078] Step 2: Pre-treat the metal base plate, clean the surface impurities with ethanol, and apply H44-61 epoxy anti-rust paint to the base surface;

[0079] Step 3: Mix nano aluminum powder, GK570, and N3390 in a mass ratio of 10:10:3, and then apply the mixed slurry to the base layer;

[0080] Step 4: Apply polyurethane resin on the base layer in step 3 by brushing. The thickness of the polyurethane resin coating is 20 μm.

[0081] Step 5: Curing the base layer obtained in step 4 at a curing temperature of 40°C.

[0082] The material obtained in this embodiment has been tested and the emissivity of the material in the 8-14μm band is 0.4. Figure 3 (b)

[0083] Example 5

[0084] The difference between this embodiment and embodiment 4 is that in step 3, the thickness of the polyurethane resin coating is 30 μm; the material obtained in this embodiment has been tested and the emissivity of the material in the 8-14 μm band is 0.5. Figure 3 (b)

[0085] Example 6

[0086] The difference between this embodiment and embodiment 4 is that in step 3, the thickness of the polyurethane resin coating is 40 μm; the material obtained in this embodiment has been tested and the emissivity of the material in the 8-14 μm band is 0.6. Figure 3 (b)

[0087] Example 7

[0088] This embodiment provides a method for preparing a low-infrared emissivity material in the mid-infrared band, comprising sequentially connecting a first low-emissivity layer, a second low-emissivity layer, an anti-rust paint layer, and a base layer. The raw materials of the first low-emissivity layer, the second low-emissivity layer, the anti-rust paint layer, and the base layer are shown in Table 1. The method specifically comprises the following steps:

[0089] Step 1: Prepare polyurethane resin by mixing component A, component B, and component C in a mass ratio of 1:1.2:1 at a mixing temperature of 20°C;

[0090] Step 2: Pre-treat the metal base plate, clean the surface impurities with ethanol, and apply H44-61 epoxy anti-rust paint to the base surface;

[0091] Step 3: Paste the ITO film on the surface of the metal base plate by pasting, wherein the thickness of the ITO film is 188 μm;

[0092] Step 4: Apply polyurethane resin on the base layer in step 3 by brushing. The thickness of the polyurethane resin coating is 20 μm.

[0093] Step 5: Curing the base layer obtained in step 4 at a curing temperature of 50°C.

[0094] The material obtained in this embodiment has been tested and the emissivity of the material in the 8-14 μm band is 0.2. Figure 3 As shown in (c), the transmittance of the material is 88.6% and the haze is 1.14%. Figure 4 As shown in the figure, the adhesion between the layers is greater than 4Mpa after testing.

[0095] Example 8

[0096] The difference between this embodiment and embodiment 7 is that in step 3, the thickness of the polyurethane resin coating is 30 μm; the material obtained in this embodiment has been tested and the emissivity of the material in the 8-14 μm band is 0.3. Figure 3 As shown in (c), the transmittance of the material is 86.7% and the haze is 2.04%. Figure 4 As shown in the figure, the adhesion between the layers is greater than 4Mpa after testing.

[0097] Example 9

[0098] The difference between this embodiment and embodiment 7 is that in step 3, the thickness of the polyurethane resin coating is 40 μm; the material obtained in this embodiment has been tested and the emissivity of the material in the 8-14 μm band is 0.4, the transmittance of the material is 85.3%, and the haze is 2.57%. Figure 4 As shown in the figure, the adhesion between the layers is greater than 4Mpa after testing.

[0099] Table 1

[0100]

[0101] It can be seen from Examples 1 to 9 that the present invention coats an anti-rust paint layer on the base layer, and the material can achieve an infrared emissivity of 0.6-0.9 in the 8-14 μm band. An anti-rust paint layer and an emissivity slurry are sequentially arranged on the base layer, and the material can achieve an infrared emissivity of 0.4-0.6 in the 8-14 μm band. An anti-rust paint layer, an ITO film, and a polyurethane resin are sequentially coated on the base layer, and the material can achieve an infrared emissivity of 0.2-0.4 in the 8-14 μm band. The low emissivity of the material can be effectively controlled by regulating the thickness of the polyurethane resin layer.

[0102] It can be seen from Examples 7 to 9 that the material of the present invention has a low low emissivity in the 8-14 μm infrared band, and its transmittance reaches a high level and the haze reaches a low level, indicating that the material has broad application prospects in the fields of infrared stealth, optical devices, and intelligent thermal management. Moreover, the adhesion between the layers of the material is greater than 4 MPa, indicating that the bonding strength between the layers of the material is high and the material stability is good.

[0103] Although the present invention is disclosed as above, the present invention is not limited thereto. Any person skilled in the art can make various changes and modifications without departing from the spirit and scope of the present invention. Therefore, the scope of protection of the present invention should be based on the scope defined by the claims.

Claims

1. A mid-infrared band low infrared emissivity material, characterized in that: It includes a low-emissivity composite layer, an anti-rust paint layer, and a base layer connected in sequence; the low-emissivity composite layer is one of a first low-emissivity layer, a first low-emissivity layer, and a second low-emissivity layer; the raw material of the first low-emissivity layer includes one or more of polyurethane resin, fluorocarbon resin, and epoxy resin; the raw material of the second low-emissivity layer is one of a conductive film and a compound slurry; the conductive film is one or more of antimony-doped tin oxide, fluorine-doped tin oxide, indium tin oxide, aluminum-doped zinc oxide, and a silver nanowire transparent film.

2. The material according to claim 1, characterized in that The polyurethane resin is a polymer resin having a carbamate group.

3. The material according to claim 2, characterized in that The polyurethane resin comprises a component A containing a polyol, a component B containing an isocyanate, and a solvent component C, wherein the component A is composed of one or more of polytetrahydrofuran, polycaprolactone diol, and polyolefin diol; the component B is composed of one or more of isophorone diisocyanate, hexamethylene diisocyanate, and isophorone diisocyanate trimer; and the component C is composed of one or more of xylene, cyclohexanone, and butyl acetate.

4. The material according to claim 3, characterized in that The mass ratio of component A, component B and component C is 1: (0.9-1.3): (1-2).

5. The material according to claim 1, characterized in that The thickness of the first low emissivity layer is 20-40 μm.

6. The material according to claim 1, characterized in that The raw material of the anti-rust paint layer is H44-61 epoxy anti-rust primer.

7. The material according to claim 1, characterized in that The compound slurry is compounded by nano-metal particles, fluorocarbon resin and curing agent. The nano-metal particles are composed of one or more of nano-silver powder, nano-aluminum powder, nano-zinc powder, nano-copper powder and nano-titanium powder. The curing agent is N3390.

8. The material according to claim 7, characterized in that The mass ratio of the nano-metal particles, fluorocarbon resin and curing agent is 8-15:10:1-5.

9. A method for preparing a mid-infrared band low infrared emissivity material according to any one of claims 1 to 8, characterized in that: The low-emissivity composite layer comprises a first low-emissivity layer and a second low-emissivity layer, wherein the raw material of the first low-emissivity layer is polyurethane resin, and specifically comprises the following steps: S1, preparing polyurethane resin; S2. Pre-treat the base layer and apply anti-rust paint to the surface of the base layer; S3, pasting or coating the raw material of the second low emissivity layer on the base layer processed in step S2; S4, coating the polyurethane resin on the base layer of step S3; S5. Curing the base layer obtained in step S4 at a curing temperature of 20-80°C.

10. A method for preparing a mid-infrared band low infrared emissivity material according to claim 9, characterized in that: In step S3 , when the raw material of the second low emissivity layer is a conductive film, it is placed on the base layer by pasting; when the raw material of the second low emissivity layer is a compound slurry, it is placed on the base layer by coating.

Citation Information

Patent Citations

  • A method for preparing a superhydrophobic coating with low infrared emissivity

    CN112920697B